Russia and the idea of the West : Gorbachev, intellectuals, and the end of the Cold War - English, Robert (Robert D.) (Columbia University Press, 2000)
An intriguing ""intellectual portrait"" of a generation of Soviet reformers, this book is also a fascinating case study of how ideas can change the course of history. In most analyses of the Cold War's end the ideological aspects of Gorbachev's ""new thinking"" are treated largely as incidental to the broader considerations of power?as gloss on what was essentially a retreat forced by crisis and decline. Robert English makes a major contribution by demonstrating that Gorbachev's foreign policy was in fact the result of an intellectual revolution. English analyzes the rise of a liberal pol.